Earnings Inequality and Other Determinants of Wealth Inequality - Benhabib, Jess; Bisin, Alberto; Luo, Mi (American Economic Review, 2017)
We study the relation between the distribution of labor earnings and the distribution of wealth. We show, theoretically as well as empirically, that while labor earnings and precautionary savings are important determinants of wealth inequality factors, they cannot by themselves account for the thick tail of (the large top shares in) the observed distribution of wealth. Other determinants, like stochastic returns to wealth, as well as savings rates and rates of returns increasing in wealth, need to be accounted for.